2017
DOI: 10.1371/journal.pone.0189952
|View full text |Cite
|
Sign up to set email alerts
|

Treating iron deficiency in patients with gastrointestinal disease: Risk of re-attendance in secondary care

Abstract: BackgroundPatients with gastrointestinal disease may have comorbid iron deficiency anaemia (IDA) and an increased risk of hospitalisation and re-attendance in hospital. The purpose of this study was to determine if oral and intravenous (IV) treatment of IDA in patients with gastrointestinal disease attending hospital were associated with differential rates of subsequent re-attendance.Methods and findingsData from the Clinical Practice Research Datalink (primary care) and Hospital Treatment Insights (secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…While cost‐effectiveness was not an endpoint of this study, a recently published cohort study of patients with gastrointestinal disease and IDA suggested a potential advantage of iv over oral iron in terms of healthcare utilisation due to lower risk of hospital re‐attendance and shorter length of stay . Our study showing rapid correction of both anaemia and iron deficiency among FCM‐treated patients with Hb levels <10 g/dL can support the identification of a feasible cut‐off when to prefer iv over oral iron in patients with gastrointestinal disease.…”
Section: Discussionmentioning
confidence: 56%
“…While cost‐effectiveness was not an endpoint of this study, a recently published cohort study of patients with gastrointestinal disease and IDA suggested a potential advantage of iv over oral iron in terms of healthcare utilisation due to lower risk of hospital re‐attendance and shorter length of stay . Our study showing rapid correction of both anaemia and iron deficiency among FCM‐treated patients with Hb levels <10 g/dL can support the identification of a feasible cut‐off when to prefer iv over oral iron in patients with gastrointestinal disease.…”
Section: Discussionmentioning
confidence: 56%
“…Although the impact of anemia on disease prognosis has not been evaluated in this specific population, anemia has been shown to increase all‐cause mortality in hospitalized cats 10 . Furthermore, anemia directly increases morbidity associated with GI disease in humans 6,29 . Not all cats with FID in our study were anemic.…”
Section: Discussionmentioning
confidence: 78%
“…10 Furthermore, anemia directly increases morbidity associated with GI disease in humans. 6,29 Not all cats with FID in our study were anemic. This finding is similar to what is observed in humans, in whom iron deficiency is diagnosed in 80% to 90% of people with chronic GI disease, with or without concurrent anemia, 1 and disease activity is independently related to iron deficiency in some forms of disease.…”
Section: Discussionmentioning
confidence: 95%
“…Most patients with gastrointestinal tumors have different negative emotions, such as fear, anxiety, and depression due to the disease itself and surgically invasive treatment; thus, the self-efficacy is poor. Such factors can harm the rehabilitation of the disease[ 16 - 19 ]. Therefore, this study implemented self-efficacy education for patients with gastrointestinal tumors during the intervention period.…”
Section: Discussionmentioning
confidence: 99%